Numerical Modelling of Building Vibrations due to Railway Traffic: Analysis of the Mitigation Capacity of a Wave Barrier - Fran Ribes-Llario; Silvia Marzal; Clara Zamorano; Julia Real (Shock and Vibration)
Transmission of train-induced vibrations to buildings located in the vicinity of the track is one of the main negative externalities of railway transport, since both human comfort and the adequate functioning of sensitive equipment may be compromised. In this paper, a 3D FEM model is presented and validated with data from a real track stretch near Barcelona, Spain. Furthermore, a case study is analyzed as an application of the model, in order to evaluate the propagation and transmission of vibrations induced by the passage of a suburban train to a nearby 3-storey building. As a main outcome, vertical vibrations in the foundation slab are found to be maximum in the corners, while horizontal vibrations keep constant along the edges. The propagation within the building structure is also studied, concluding that vibrations invariably increase in their propagation upwards the building. Moreover, the mitigation capacity of a wave barrier acting as a source isolation is assessed by comparing vibration levels registered in several points of the building structure with and without the barrier. In this regard, the wave barrier is found to effectively reduce vibration in both the soil and the structure.